THE ROLE OF MOTIVATION IN THE SPORTSMAN'S ACTIVITY ("Conference on Universal Science Research 2023", 2023)
This article discusses the role of psychology in any field, any profession, including in the field of sports, and most importantly, the role of motivation in an athlete's activity.